Modelling flow and transport to assess the influence of subsurface geometry on Alpine karst aquifer vulnerability - Fleck, Barbara (Acta carsologica, 2025)
Karst areas are highly susceptible to contamination due to rapid recharge and throughflow caused by their heterogeneous structure with unknown networks of conduits embedded in a matrix of low conductivity. Vulnerability methods have been used to ensure adequate protection of drinking water resources. However, most of the studies assessing the vulnerability of karst aquifers consider it as a constant value in time and, therefore, under special hydrological conditions in space, which is an oversimplification of reality. In this work, the behaviour of an Alpine karst system characterised by rapid flow and transfer through vertical shafts has been studied by discrete numerical modelling using MODFLOW 6. Six numerical models have been designed with the aim of representing simple common geometrical configurations found in Alpine karst systems. These models simulate how the flow and transport response at the system outlet is influenced by the aquifer geometry and recharge conditions. The results confirm that the arrival of the tracer at the spring strongly depends on the conduit geometry and the recharge conditions. This demonstrates that karst aquifer vulnerability cannot be defined as a constant value but should be specifically assessed depending on the spatio-temporal conditions.
Keywords: Alpine karst system; MODFLOW 6; numerical flow and transport modelling; numerično modeliranje pretoka in prenosa; overflow; preplavljanje; ranljivost; sistem alpskega krasa; vulnerability